THE EFFECT OF VIRGIN COCONUT OIL (VCO) APPLICATION ON DIAPER RASHES IN INFANTS AT THE UPTD PUSKESMAS SINDANG JAYA, TANGERANG DISTRICT 2023 - Irna Harisa; Mizwar Taufiq pirmansyah (Universitas STRADA Indonesia, 2023)
Diaper rash is a rash that causes inflammation in the area affected by the diaper , namely the thighs, buttocks and anal area, causing candida infection. This is a common skin disease in infants and children when diapers are always wet and are rarely changed. To determine the effect of giving Virgin Coconut Oil (VCO) on diaper rash. In this study using quantitative research methods using pre-experimental methods with the One Group Pretest-posttest approach . It is known that the mean before and after being given treatment is 0.281 with a standard deviation value of .457. On the test results of the paired sample T test, the t-count value is 3.483, so the value outside the acceptance area of Ho is rejected and Ha is accepted. This study shows that there is a good effect of giving Virgin Coconut Oil (VCO) to babies who experience diaper rash.